Military Sexual Trauma and Risky Behaviors: A Systematic Review. (October 2021) - Forkus, Shannon R.; Weiss, Nicole H.; Goncharenko, Svetlana; Mammay, Joseph; Church, Michael; Contractor, Ateka A.
Introduction: Military sexual trauma (MST) is a serious and pervasive problem among military men and women. Recent findings have linked MST with various negative outcomes including risky, self-destructive, and health-compromising behaviors. Objective: The current review summarizes the existing literature on the association between MST and risky behaviors among military men and women who have served in the U.S. Armed Forces. Method: We systematically searched five electronic databases (PubMed, EMBASE, PSYCINFO, PILOTS, and CINAHL Plus) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Of the initial 2, 021 articles, 47 met the inclusion criteria. Reviewed studies revealed three patterns of findings: (1) largely studied and consistent (i.e., suicidal behaviors, disordered eating), (2) mixed and in need of future research (i.e., alcohol and drug use, smoking), and (3) underexamined (i.e., sexual behaviors, illegal/aggressive behaviors) or completely neglected (e.g., problematic technology use, gambling). Discussion: The current systematic review advances literature by providing strong support for an association between MST and a wide range of risky behaviors. Moreover, it highlights important areas for future research.